KARAKTERISTIK DIREKSI DAN SENTIMEN LAPORAN TAHUNAN - Vania Clarensia Budiono; Ari Budi Kristanto (ITB AAS INDONESIA, 2022)
Companies disclose internal information through various forms (e.g. numeric, text, images, audio, video) and mediums (e.g. financial statements, website, social media, press releases, etc). Numerical data have been empoyed so much for accounting and financial analysis. On the other hand, the most abundant data type (i.e. textual data) has not been utilized extensively. Furthermore, the textual information is also important to assist the interpretation of financial information. Therefore, this study aims to see whether the characteristics of the directors (age and gender) will affect the tone/sentiment in the annual report. This study use manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 as the object. Using purposive sampling method, there are 99 companies (495 research observations) that were choosen as the sample. The sentiment analysis of the annual report was done using textual analysis based on the lexicon approach. The lexicon assessment was particularly based on the VADER method on Orange Data Mining software. The results showed that the age of the board of directors (BOD) had a significant positive effect on the positive sentiment of the annual report. However, this study could not found the impact of BOD gender on the positive sentiment.